College Made Whole : Integrative Learning for a Divided World - Gallagher, Chris W. (Book collections on Project MUSE., 2019)
"This optimistic big-idea book about the philosophy and organization of higher education explains how universities can form creative, adaptive, and integrative graduates who are ready to take on the complex, systemic problems of the contemporary world. The author argues against those who propose to unbundle higher education institutions into discrete providers of goods and services who aim to prepare students for existing professions"